Developing and implementing Picture-Based Advisories (PBA) for farmers in Kenya - Ceballos, Francisco; Kramer, Berber; Kivuva, Benjamin (International Food Policy Research Institute, 2022)
IFPRI’s picture-based insurance (PBI) initiative, recognized as a CGIAR@50 Innovation and active since 2016, relies on participating farmers to upload smartphone pictures of their fields at intervals throughout the growing season. In the event of bad weather, pests, disease, or other problems that harm the crops, the photos are used to assess the damage and trigger insurance payouts.